Low prevalence of knee chondrocalcinosis and its catabolic association with serum matrix metalloproteinase 3: A rural Japanese population study. (24th March 2017) - Chiba, Daisuke; Tsuda, Eiichi; Sasaki, Eiji; Takahashi, Ippei; Nakaji, Shigeyuki; Ishibashi, Yasuyuki
Abstract: Aim: This study aimed to elucidate the prevalence of radiographic knee chondrocalcinosis (CC) and to clarify whether CC is correlated with self‐reported knee symptoms and a serum catabolic biomarker. Methods: A total of 1278 volunteers participated. Plain radiographs of both knees were obtained. Identification of a linear calcification in the knee joint space was defined as CC. Patients with a Kellgren‐Lawrence grade of 2 or more were considered to have knee osteoarthritis (OA). Symptoms were evaluated using the Knee injury and Osteoarthritis Outcome Score (KOOS) Pain scale, and serum matrix metalloproteinase‐3 (MMP‐3) concentration was determined. Multiple regression analysis was conducted to determine whether CC was correlated with OA, the KOOS Pain scale and MMP‐3 concentration. Results: Twenty‐eight subjects were found to have CC (2.2%), and 389 had OA (30.4%). CC was correlated with OA (odds ratio: 5.797; P = 0.006). Additionally, CC was correlated with MMP‐3 concentration (B = 11.415, β = 0.059, P = 0.014), but not with KOOS Pain scale. Conclusions: The prevalence of CC was low in the Japanese population evaluated in this study. While CC was not correlated with self‐reported knee symptoms, it was positively correlated with serum MMP‐3 concentration.